Sexual size dimorphism, spatial segregation and sex-biased bycatch of southern and northern royal albatrosses in pelagic longline fisheries. Issue 2 (26th October 2016) - Jiménez, Sebastián; Domingo, Andrés; Brazeiro, Alejandro; Defeo, Omar; Abreu, Martin; Forselledo, Rodrigo; Phillips, Richard A.
Abstract: Bycatch in longline fisheries is a major contributor to the global decline of albatrosses. Sexual segregation at sea often leads to unequal overlap with different fisheries, resulting in sex-biased bycatch, exacerbating the impact on a population level. In great albatrosses ( Diomedea spp.), males (the larger sex) tend to spend more time at higher latitudes than females, attributed to competitive exclusion or differences in flight performance mediated by the pronounced sexual size dimorphism (SSD). Consequently, larger numbers of females are bycaught in pelagic longline fisheries in subtropical and temperate areas. Although this has been shown for Diomedea exulans, it has not been confirmed for all great albatross species. Here we examined the degree of SSD and developed discriminant functions to determine species and sex in D. epomophora and D. sanfordi ; species that are often killed in several fisheries in the Southern Hemisphere. Based on a large sample of albatrosses bycaught off Uruguay, both species showed substantial SSD. Discriminant functions assigned species and sex to otherwise indeterminate individuals with 90–100% accuracy. Based on all birds identified ( n =128), bycatch in the pelagic longline fishery was female-biased, indicating sexual segregation at sea. The discriminant functions presented enable species and sex to be identified, providing critical data for future bycatch assessments.